Updating the Education of Talented Children - Fathurrohman, Mukhlis (LENTERNAL: Learning and Teaching Journal, 2023)
Naturally, each child is unique, has individual diversity, and differs from each other in various ways, such as in terms of intelligence, talent, personality, and physical and spiritual condition. Based on the diversity of such characteristics, it is necessary to pay attention to educational models that can facilitate the development of children according to their unique characteristics. Including education for children with superior abilities or children with talent, the education of talented children is an integral part of the national education system. Through the Ministry of Education, children have the greatest opportunity to develop according to their potential. If every child has been able to realize their own potential, at that time they will become self-reliant, productive, and contributing human beings, capable of making a very meaningful contribution to the improvement of the quality of life of a nation based on the noble values that are upheld and cherished by the entire Indonesian nation.